How to handle conflict and confrontation - Spano, Sharon; National Seminars Group (Buffalo, N.Y. : Kineticvideo : Sound Learning Solutions, 2000)
Training video offers techniques to help resolve conflict in a business environment
Title from title screen
Trainer: Sharon Spano
Keywords: Conflict management; Interpersonal confrontation; Interpersonal conflict